2008
DOI: 10.1002/jssc.200700470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of separation in gradient elution ion chromatography by combining several retention models and objective functions

Abstract: Original PaperEvaluation of separation in gradient elution ion chromatography by combining several retention models and objective functions In this work, three different methods for modeling of gradient retention were combined with several optimization objective functions in order to find the most appropriate combination to be applied in ion chromatography method development. The system studied was a set of seven inorganic anions (fluoride, chloride, nitrite, sulfate, bromide, nitrate, and phosphate) with a KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This approach, taken from literature, 16,19 is based on summation of contributions of small timeintervals inside which the retentions were calculated by use of experimentally obtained isocratic models. The isocratic models were 2 nd order polynomial correlations of analyte retention coefficient logarithm, logk, and eluent concentration logarithm, logc.…”
Section: Optimization Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, taken from literature, 16,19 is based on summation of contributions of small timeintervals inside which the retentions were calculated by use of experimentally obtained isocratic models. The isocratic models were 2 nd order polynomial correlations of analyte retention coefficient logarithm, logk, and eluent concentration logarithm, logc.…”
Section: Optimization Methodologymentioning
confidence: 99%
“…18,19 The aim of this work is application of computerassisted methodology in rapid method development process for IC determination of inorganic cations in surface water. Gradient elution retention model was used to predict resolution and peak asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs can also be used as the basis of computer-assisted optimization method for selection of optimal gradient conditions for anion separations in chromatography [39][40][41]. The ANNs with 1-10-9 architecture has been found to be rapid and accurate in predicting retention times for anions in linear gradient elution ion chromatography with hydroxide eluents.Tham et al applied ANNs in quantitative structuregradient elution retention relationship of the compounds such as phenyl thiocarbamyl amino acids derivatives with estimation of the chromatographic retention times [42].…”
Section: Anns Applications Analytical Data Analysis and Structure Retmentioning
confidence: 99%
“…We have shown that, at least for the studied solution/stationary phase system in the studied concentration range, they are sufficient to describe the whole peak, including prediction of individual peak asymmetry as well as chromatographic resolution between adjacent peaks 37. Generalized logistic function was used for this purpose; it is rather simple and its three parameters A , B , and C can be easily calculated from the abovementioned three characteristic points of the experimental distribution curve 38.…”
Section: Integrated Approach Descriptionmentioning
confidence: 99%
“…A number of different theoretical and empirical models for the prediction of characteristic chromatographic parameters (retention, resolution, efficiency, etc.) and the determination of optimal separation conditions have been brought out 1–16 in the last few decades. Some of them became bases of different optimization software (Drylab 17, Preopt‐W 18, 19, Osiris 20, Michrom 21, 22, Chromsword 23, and Virtual column 24).…”
Section: Introductionmentioning
confidence: 99%